Analisis Pernikahan Beda Agama tentang Pandangan Hukum Positif Agama dan Sosiologi - Arief, M. Rahmad; Yohanes; Setiawan, Andre; Mustapid, Hidayatul; Permana, Hadi Jaya; Febrianty, Yenny; Kholik, Acep Abdul (Indonesian Journal of Law and Justice, 2023)
Marriage is a bond of agreement between human individuals to build a household ship with a happy and eternal goal until the end of their life. In a marriage, there are many factors supporting similarities, differences, economics, religion, social status and so on. Our aim is to research to find out whether it is permissible to marry religious differences are in accordance with the results of the methodology that we are looking for, namely in accordance with the perfective Indonesian positive law, religious law and sociological views on interfaith marriages. Indonesia has its own regulations which are regulated in its law book in the Civil Code, while according to the perspective of religious law in Indonesia, marriages from people of different religions are not allowed, they are considered invalid or forbidden, the sociological view of marriages between different religions is considered valid. Just because in social science a marriage occurs because of mutual love and does not prioritize religion because love occurs because there are similarities and differences that complement each other and there is an attitude of tolerance between partners so that the marriage is eternal and happy.